2004
DOI: 10.1210/me.2003-0489
|View full text |Cite
|
Sign up to set email alerts
|

A Splice Variant of the Human Luteinizing Hormone (LH) Receptor Modulates the Expression of Wild-Type Human LH Receptor

Abstract: We previously reported a splice variant form of human LH receptor [hLHR(exon 9)] that lacks exon 9, coding the N-terminal extracellular region close to the first transmembrane domain. Several recent studies suggest that G protein-coupled receptors are able to form dimerization or oligomerization of the receptor, suggesting an intermolecular interaction between hLHR(exon 9) and the wild-type LH receptor (hLHR). The aim of this study, using coimmunoprecipitation, is to examine whether hLHR forms an association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 35 publications
4
44
1
Order By: Relevance
“…In the present study we demonstrate that the common splice variant comprising a large portion of the N-terminal extracellular domain of the receptor can regulate expression of the full-length receptor in a heterologous expression system in mammalian cells. Similar findings have been reported in the past for a few other GPCRs (Grosse et al, 1997;Karpa et al, 2000;Sarmiento et al, 2004) and recently also for another LHR variant (Nakamura et al, 2004). Thus, regulation of GPCRs by their corresponding splice variants may be a more common phenomenon than has been anticipated.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study we demonstrate that the common splice variant comprising a large portion of the N-terminal extracellular domain of the receptor can regulate expression of the full-length receptor in a heterologous expression system in mammalian cells. Similar findings have been reported in the past for a few other GPCRs (Grosse et al, 1997;Karpa et al, 2000;Sarmiento et al, 2004) and recently also for another LHR variant (Nakamura et al, 2004). Thus, regulation of GPCRs by their corresponding splice variants may be a more common phenomenon than has been anticipated.…”
Section: Discussionsupporting
confidence: 89%
“…It can be hypothesized that misrouting of the full-length receptor might be a consequence of its interaction with the variant. In agreement with this possibility, Nakamura et al (2004) have shown that the human LHR splice variant lacking exon 9 interacts with and can alter expression of the full-length LHR as well as that of another glycoprotein hormone receptor, the follicle-stimulating hormone receptor (Yamashita et al, 2005). Furthermore, the recently reported crystal structure of the truncated follicle-stimulating hormone receptor ectodomain and its cognate hormone reveal that the ectodomain is able to dimerize in the absence of the C-terminal half of the protein (Fan and Hendrickson, 2005).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The variants reported include a complete deletion of exon 10 and/ or partial deletion of exon 11, and there is also a loss of exon 3 in bovine granulosa cells (Nogueira et al 2007). In humans, a splice variant lacking exon 10 produces a protein capable of binding hCG, but not LH (Müller et al 2003) and, in keeping with a further human splice variant lacking exon 9, can form complexes with other LHCGR isoforms to reduce overall receptor expression and cAMP accumulation (Nakamura et al 2004, Ndiaye et al 2005, Minegishi et al 2007. Primer design in this study (Table 1) allowed us to confirm the expression of LHCGR transcripts lacking exons 3 and 9; however, we were unable to detect transcripts lacking exon 10 in any of the somatic (i.e.…”
Section: Molecular Basis Of Luteal Support and Steroidogenesismentioning
confidence: 99%